Effect of referral on mortality in trauma victims admitted in trauma centre of Chattrapati Shahuji Maharaj Medical University: A one year follow up study. Issue 1 (January 2014) - , V Verma; Gupta, K; Singh, GK; Kumar, S; Shantanu, K; Kumar, A
No abstract available